Solar Power Station For High-Powered Electronics - Putri, Tika Erna; Suhono, Suhono; Aji, Rahmadi Putra; Aji, Wahyu Waskito (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2024)
The number of PLN power users below 2200 VA for households in Indonesia causes the use of high-powered electronic equipment (HPE) such as electric stoves, microwaves, and ovens, to be limited. In some cases, the HPE can't operate due to lack of power or being the cause of the miniature circuit breaker (MCB) down. In fact, the use of HPE can improve the quality of life of people. Power stations separated by PLN (off-grid) and high-powered are thought to be able to solve the problem due to the daily use of HPE mostly over 1-3 hours. Solar home system (SHS) can be the base power station off-grid for HPE. However, the SHS studies carried out are limited to low power below 1000 VA or high power above 3000 VA. Addressing this, the study will create high power stations between 1000 VA - 3000VA based on SHS and analyze its daily use for electrical HPE equipment such as electric stoves, microwaves, and ovens. The charging of a power station with four 100 Wp Polycrystalline solar panels can charge around 1 kWh on sunny days in Yogyakarta, Indonesia. Daily cooking activity shows the power station can support 2-3 menus daily with the usage of HPEs.